2015
DOI: 10.3382/ps/pev254
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic eggshell thickness measurement for selection of layers

Abstract: This study aimed to develop a methodology for using ultrasonic technology (USG) to record eggshell thickness for selection of layers. Genetic correlations between eggshell strength and its thickness have been reported to be around 0.8, making shell thickness a selection index candidate element. Applying ultrasonic devices to measure shell thickness leaves an egg intact for further handling. In this study, eggs from 2 purebred populations of Rhode Island White (RIW) and Rhode Island Red (RIR) hens were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…The relationship between eggshell strength and eggshell thickness is very important to overall shell measurements and might differ according to the thickness of the shell. Kibala et al (2015) observed a genetic correlation between eggshell strength and its thickness was around 0.8, making the shell thickness a selection index candidate element. Ketta and Tumova (2017) indicated that ΔE* ab = √[(ΔL*) doi: 10.17221/75/2017-CJAS the eggshell strength was significantly increased as the eggshells became thicker.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between eggshell strength and eggshell thickness is very important to overall shell measurements and might differ according to the thickness of the shell. Kibala et al (2015) observed a genetic correlation between eggshell strength and its thickness was around 0.8, making the shell thickness a selection index candidate element. Ketta and Tumova (2017) indicated that ΔE* ab = √[(ΔL*) doi: 10.17221/75/2017-CJAS the eggshell strength was significantly increased as the eggshells became thicker.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Yan et al (2014) studied the relationship between the uniformity of eggshell thickness and eggshell quality of Lohmann Brown eggs and reported that the uniformity of eggshell thickness is positively correlated with eggshell thickness (0.297), breaking strength (0.430), static stiffness (0.409), and fracture toughness (0.171) which might be used as an important indicator for other shell measurements in poultry breeding. Kibala et al (2015) developed a new methodology using ultrasonic technology to record eggshell thickness at different egg latitudes. The authors observed a genetic correlation between eggshell strength and its thickness to be around 0.8, making shell thickness a selection index candidate element.…”
Section: Eggshell Quality and Its Measurementsmentioning
confidence: 99%
“…They also indicated that, eggs with thin but more uniform eggshell were stronger than those with thick but less uniform eggshell. Moreover, Kibala et al (2015) reported a higher genetic correlations (0.8) between eggshell strength and its thickness making shell thickness as a selection index candidate element. However, thicker eggshells do not guarantee stiffer or stronger eggs (Bain 2005).…”
Section: Introductionmentioning
confidence: 99%